The rhythm of making cheaps: a case study of rhythmanalysis and qualitative labour shortages in Canadian fisheries. Issue 2 (4th May 2021) - Knott, Christine
ABSTRACT: This paper explores how an intersectional rhythmanalysis approach that includes attention to animals, ecosystems and corporate capital investment strategies can provide crucial insight into reported labour shortages. This paper unpacks the systemic relations of difference and power among mobile workers by highlighting the reorganization of temporal rhythms of work and life, but also animals and environments, that work to create or reproduce immobility and enclosure. Drawing on interview data and document analysis related to the seafood processing sector, the paper argues that the construction of qualitative labour shortages is tied to racialized, gendered and classed workers who are migrant or mobile. Critically, this includes new rhythms of capital accumulation, and related arrhythmias in the work/home lives of local and interprovincial migrant Canadian workers, through changes to schedules and seasonal contracts. These rhythmic changes make employment in these plants less desirable or feasible for these workers and support employers' claims of labour shortages.